The Integration of AI in English for Nursing Instructions: A Systematic Literature Review - Puspasari, Atika; Agustina, Noni (JET (Journal of English Teaching), 2025)
The integration of artificial intelligence (AI) in English for Nursing instruction has become increasingly important as healthcare becomes more technologically driven and globally connected. This systematic review analyzes 28 studies published between 2022-2024 to examine the current state of AI implementation in nursing ESP education. The findings reveal three distinct categories of technological integration: basic digital tools (54%), intermediate AI integration (32%), and advanced AI applications (14%). While the analysis shows promising benefits in personalized learning and authentic communication practice, significant challenges persist in infrastructure, teacher expertise, and resource allocation. The review identifies a notable gap between available AI technologies and their practical classroom implementation, with 82% of studies reporting infrastructure limitations. These findings suggest that while AI integration shows great potential for transforming nursing ESP education, substantial work remains to bridge the gap between technological capabilities and practical implementation.